Muslim networks and transnational communities in and across Europe - Allievi, Stefano; Nielsen, Jørgen S. (Brill, 2003)
The topic of this collection of articles is the increasingly transnational nature of Islam in Europe as well as the mechanisms by which the transnationalism is activated, especially the media. The papers integrate specific case studies with more general and thematic considerations.
Keywords: Muslims -- Europe.; Europe -- Ethnic relations.; Islam in mass media.; Minorities -- Europe.; Muslims -- Cultural assimilation -- Europe.; Musulmans -- Europe.; Islam dans les médias.; Minorités -- Europe.; Musulmans -- Acculturation -- Europe.; Europe -- Relations interethniques.; SOCIAL SCIENCE -- Discrimination & Race Relations.; Ethnic relations; Islam in mass media; Minorities; Muslims; Muslims -- Cultural assimilation; Europe; Globalisierung; Islam; Kommunikationsstruktur; Aufsatzsammlung; Europa; Islamieten.; Sociale netwerken.; Minderheden.; Acculturation.; Conflit culturel.; Diaspora.; Islam.; Mass-média.; Minorité religieuse.; Musulman.; Relations interreligieuses.; Transnationalisme.; Europe.